Landing kinematics of parallel bars dismounts - Geiblinger, H.; Morrison, W. E.; McLaughlin, P.; Wrigley, T. V. (Proceedings of the First Australasian Biomechanics Conference, 1996, Sydney, 1996)
The purpose of this study was to (a) describe the linear and angular kinematics, and temporal characteristics involved in the execution of landings; and (b) identify kinematic parameters crucial for controlled and stable landings on the parallel bars. Results: The landings on parallel bars represented double back somersaults tucked and piked with a backward horizontal velocity. Analysis of the data revealed a mean maximum CM height during dismount of 2.530.10m. The mean CM height at landing touch-down was 0.740.05m and the mean minimum CM height was 0.570.08m. The mean CM vertical impact velocity was -5.420.42m/s, horizontal velocity backwards was 0.430.25m/s, and horizontal velocity sidewards was 0.690.17m/s. The mean angle of CM to ground contact (toes) and the horizontal at landing touch-down was 866. The mean knee angle at landing touch-down was 15810 and minimum knee angle was 10226. The mean landing phase duration (CM height at landing touch-down to CM height minimum) was 0.110.03 seconds over a distance of 0.17 m and 56. The mean angular velocities of the hip, knee, and ankle were -22183, -692217, and -249109 /sec., respectively. It is concluded that successful landings are likely when efforts are made to achieve (a) a high maximal vertical velocity at release; (b) a tight tuck/pike position in the double back somersault near the peak of the flight to accomodate the rotational equirements of the flight phase; (c) an early preparation for a controlled and stable landing; and (d) optimal body segment coordination and timing in reducing all body momentum to zero during the landing phase. Selected parameters of the results presented in this study may be used to form a representative biomechanical profile for parallel bars landings. (from: Proceedings of the First Australasian Biomechanics Conference; ISBN 0 86758 999 X)